Anterior visual pathway assessment by magnetic resonance imaging in normal-pressure glaucoma - Zhang, Ya-Qin; Jonas, Jost B. (Acta ophthalmologica, 2012)
Abstract. Purpose: To analyze the axonal architecture of the optic nerve in patients with normal-pressure glaucoma and determine whether these parameters correlate with the disease severity. Methods: Using magnetic resonance (MRI) imaging (1.5-Tesla unit) and diffusion tensor (DT) MRI, we measured the optic nerve diameter, optic chiasm height and lateral geniculate nucleus (LGN) volume in patients with normal-pressure glaucoma and an age-matched control group. The retinal nerve fibre layer thickness (RNFL) was determined by optical coherence tomography (OCT). Results: The study included 30 patients with normal-pressure glaucoma and 30 age-matched control subjects. Optic nerve diameter (p < 0.001), optic chiasm height (p < 0.001) and LGN volume (p = 0.02) were significantly smaller in the glaucoma group than in the control group and were significantly correlated with RNFL thickness and perimetric loss. In the control group, the parameters significantly (p < 0.05) decreased with age. The DT-MRI-derived fractional anisotropy for the optic nerve was significantly lower (p < 0.001), and the DT-MRI-derived mean diffusivity (p < 0.001), radial diffusivity (λ⊥; p < 0.001) and axial diffusivity (λ||; p = 0.009) for the optic nerve were significantly higher in the glaucoma group and significantly correlated with RNFL thickness and mean perimetric defect. Conclusions: Patients with normal-pressure glaucoma show an age-adjusted reduced optic nerve diameter, optic chiasm height and LGN volume as measured by MRI, correlating with a reduced RNFL thickness and increased perimetric loss. MRI may be applied to examine the optic nerve in patients with glaucoma with opaque optic media.
Gesehen am 01.08.2018